2008
DOI: 10.1038/ejcn.2008.6
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption is not related to the metabolic syndrome at the age of 36 years: the Amsterdam Growth and Health Longitudinal Study

Abstract: Background/Objectives: Coffee consumption has been postulated to decrease the risk of diabetes mellitus type II. The longterm effects of coffee consumption on the metabolic syndrome (MS) and its components are unknown. This study investigated the relationship of long-term coffee consumption between the age of 27 and 36 years with the prevalence of the MS at the age of 36 years. Subject/Methods: Data on coffee consumption and the MS components were derived from a healthy sample of 174 men and 194 women followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
1
38
0
1
Order By: Relevance
“…Previous studies showed the significant association between higher decaffeinated coffee consumption and lower HbA 1c levels among women with type 2 diabetes [45], whereas no significant associations were seen in other population-based studies [16,46].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies showed the significant association between higher decaffeinated coffee consumption and lower HbA 1c levels among women with type 2 diabetes [45], whereas no significant associations were seen in other population-based studies [16,46].…”
Section: Discussionmentioning
confidence: 96%
“…Despite numerous studies on these diseases, studies of healthy volunteers regarding MetS-related biomarkers are relatively few and inconclusive. One study conducted on a Japanese population over the age of 40 y showed an inverse association between coffee consumption and MetS [15], whereas a study conducted on a younger European population, ages 27 to 36 y, showed no relation [16]. In these studies, waist circumferences were compared with the effects of coffee consumption on central obesity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, only a few studies have examined the relationship between coffee consumption and the risk of developing metabolic syndrome. 17 , 18 One cross-sectional study showed that habitual coffee consumption was inversely associated with metabolic syndrome and its components among Japanese elderly adults. 17 Another longitudinal study, which followed a Dutch population for 9 years, found no association between coffee consumption and the development of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…17 Another longitudinal study, which followed a Dutch population for 9 years, found no association between coffee consumption and the development of metabolic syndrome. 18 …”
Section: Introductionmentioning
confidence: 99%